A critical analysis of the development of the public benefit requirement of charitable purposes under English and Welsh charity law, from Re Compton [1945] 1 Ch 123 to R (Independent School Council) v Charity Commission [2012] Ch 214. Issue 1 (January 2016) - Cubillo Barsi, Naomi
Abstract : The enactment of the Charities Act 2006 in November 2006 introduced the first statutory definition of charity into English and Welsh law. Under the provisions of the Act, charitable status requires that an institution must be established for charitable purposes only and that the charitable purposes must be of public benefit. Although, generally, well received the Charities Act 2006 has been criticised as 'flawed' on the public benefit requirement of charitable purposes. The Charities Act 2006 was passed with the principle aim of modernising existing charity law, which was considered outdated and unclear. However, unlike charitable purposes, which are set down within the provisions of the Act, a definition of public benefit is not provided. Section 3(3) of the Charities Act 2006 merely provides that 'reference to public benefit is a reference to the public benefit as that term is understood for the purposes of the law relating to charities in England and Wales'. This lack of a definition as to what constitutes public benefit and statutory reliance upon the charities' regulator, the Charity Commission, to interpret and provide guidance on the public benefit requirement for charitable purposes has led to criticism that the Charities Act 2006 has raised as many uncertainties as it sought to clarify. In critically evaluating the impact of the Charities Act 2006, and its successor, the Charities Act 2011, upon English charity law, this assessment places the legal definition of charity within its complex and, at times, vague historical context. Thus, providing an ideal backdrop in which to explore the policy objectives behind the Charities Acts and assess the effectiveness of the Charities Acts in achieving those objectives.